Rebranding Ma’Ayu Batik Probolinggo sebagai Upaya Peningkatan Brand Awareness - R Muhammad Hanafi Imanuddin; Gunawan Susilo; Yon Ade Lose Hermanto (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: Since it was first established until 2021 Ma'ayu Batik still does not have a consistent brand identity that can represent the product. The business only relies on the superiority of its batik products without thinking about the importance of corporate identity to spark the audience to glance at these products. The purpose of this design is to create a brand identity to increase awareness. The method used by Alina Wheeler has five stages for designing, namely: conducting research, clarifying strategy, designing identity, creating touchpoints, and managing assets. The results of this design are in accordance with the existing problem formulations, resulting in a Graphic Standard Manual (GSM). GSM contains the concept of brand identity, the language used for communication, font selection, supergraphics and the implementation of identity on the media. Keywords: Ma’ayu Batik, brand identity, awareness Abstrak: Sejak pertama kali didirikan hingga 2021 Ma’ayu Batik masih belum memiliki brand identity yang konsisten yang dapat merepresentasikan produk. Usaha tersebut hanya mengandalkan keunggulan dari produk batiknya saja tanpa memikirkan pentingnya identitas korporat untuk memantik audiens agar melirik produk tersebut. Tujuan perancangan ini menciptakan brand identity untuk meningkatkan awareness. Metode menggunakan milik Wheeler (2013) yang mempunyai lima tahap untuk melakukan perancangan yaitu: conducting research, clarifying strategy, designing identity, creating touchpoints, and managing assets. Hasil perancangan ini sesuai dengan rumusan masalah yang ada, menghasilkan Graphic Standard Manual (GSM). GSM tersebut memuat konsep brand identity, bahasa yang digunakan untuk komunikasi, pemilihan font, supergraphic dan implementasi identitas terhadap media. Kata kunci: Ma’ayu Batik, brand Identity, awareness